KEMAMPUAN MEMBACA PEMAHAMAN WACANA ARAB MELAYU MAHASISWA PROGRAM STUDI PENDIDIKAN AGAMA ISLAM SEKOLAH TINGGI AGAMA ISLAM SULTHAN SYARIF HASYIM SIAK SRI INDRAPURA - Fauziah, Indah; Rahmah, Nadia; Yahfis, El Firdausia; Faizah, Hasnah (AL - IBRAH, 2022)
On the basis of a sense of responsibility and concern for the problem of ability in language skills and the lack of interest and motivation of students in studying Arabic Malay which is integrated with the Riau Malay Culture course which is only studied once during their study period, the researcher is sensitive and motivated to conduct research on one of the one language skill associated with Arabic-Malay teaching, namely the skill of reading comprehension of Arabic-Malay discourse. The problem in this study is how the ability to read and understand Arabic-Malay discourse of students of the Islamic Religious Education Study Program at the Islamic College of Sulthan Syarif Hasyim Siak Sri Indrapura. Researchers provide limitations on the ability to read comprehension, namely the ability to determine the four aspects of reading comprehension including: main ideas, explanatory ideas, messages/mandates, and conclusions in Arabic-Malay discourse. This study aims to determine and describe the ability to read Arabic-Malay discourse comprehension in the four aspects of reading comprehension. The method used in this study is a descriptive method with a research sample of 30 students in the fifth semester of the Islamic Religious Education Study Program, Sulthan Syarif Hasyim Siak Sri Indrapura Islamic College for the 2022/2023 Academic Year. This sampling is known as a full sample or 100% of the total research population. The data collection technique used in this study was an objective test technique (multiple choice questions). Data analysis techniques by collecting test results, providing assessments according to the scoring reference, finding the percentage of each aspect of reading comprehension, and finding/calculating the average value. The results of the study concluded that the ability to read Arabic-Malay discourse varied, namely (1) the ability to determine main ideas was in the low category with an average of 25.00 (2) the ability to determine explanatory ideas was in the low category with an average of 26.67 (3) the ability to determine messages/mandates was in the low category with an average of 45.00 and (4) the ability to determine conclusions is in the low category with an average of 8.33. Overall, the ability to read and understand Arabic-Malay discourse among students of the Islamic Religious Education Study Program at the Islamic College of Sulthan Syarif Hasyim Siak Sri Indrapura is in the low category with an average of 26.25.